Pengembangan Video Pembelajaran Berbasis PMRI untuk Mendukung Mental Calculation Siswa dalam Permasalahan Aritmatika Sosial - Meryansumayeka, Meryansumayeka; Yusuf, M.; Suganda, Vina Amilia (Jurnal Elemen, 2018)
This study aims to develop a PMRI-based Social Arithmetic learning video in the junior high school that is valid, practical, and has a potential effect to support the mental calculation of junior high school students in Social Arithmetic issues. This type of research is a modified development study between Rowntree and Tessmer. There are 3 stages in this research namely planning stage, development stage, and evaluation phase. In the development process, this research involves experts as validators of a learning video developed. The subjects of this study are students of grade VII Islamic Junior High School Raudhatul Ulum Sakatiga Indralaya as many as 22 people. The result of this research shows that the learning video developed by this researcher is valid by the experts who tested 3 aspects i.e. material aspect, media display and instructional design; practice based on result of one to one scale that is testing the product on 3 students with different skills and on a small group scale of 6 people; and having a potential effect to support students mental calculation in social arithmetic problems.